Mekanisme Corporate Governance Dan Nilai Perusahaan - Nia Yuniarsih (BIP's JURNAL BISNIS PERSPEKTIF, 2014)
The objective of this study is to examine the influence of corporate governance mechanism, namely managerial ownership, institutional ownership, to firm value. This study takes sample from 32 companies in the manufacturing sector at the Indonesia Stock Exchange, which were published in financial report from 2012-2013. The method of analysis of this research used multi regression and single regression. The results of this study show that (1) managerial ownership had positive significant influence to firm value, (2) institutional ownership had not significant influence to firm value, (3) simultaneously of managerial ownership, institutional ownership, had significant influence to firm value.